2011
DOI: 10.1007/s00198-011-1570-9
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific differences in bone mineral density in black and white premenopausal South African women

Abstract: FN and TH BMD were higher, but LS BMD was lower in black than white South African women with body composition, lifestyle and SES factors contributing differently to BMD in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
4
19
2
Order By: Relevance
“…Our findings of a positive association between lean mass and BMD are in keeping with those of Amarendra et al (27) in their study of AI men, Chantler et al (7) in BA women, and others (33). This is the first report of the significant contribution of lean mass to BMD in black South African men.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings of a positive association between lean mass and BMD are in keeping with those of Amarendra et al (27) in their study of AI men, Chantler et al (7) in BA women, and others (33). This is the first report of the significant contribution of lean mass to BMD in black South African men.…”
Section: Discussionsupporting
confidence: 94%
“…A recent comparison of fractures in adolescent mother-daughter pairs noted that white adolescents and their mothers had more fractures compared with black adolescent mother-daughter pairs (4). Ethnic differences in BMD have been reported with black South African females having higher BMD at the femoral neck (femoral) than their white counterparts and similar BMD at the lumbar spine and distal radius (5,6), whereas a more recent study has reported higher BMD at the femoral and hip but lower lumbar BMD in black than white women (7). It is possible that ethnic differences in BMD contribute to differences in fracture rates; however, to our knowledge similar data are not available for BA men or AI subjects.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Endurance exercise training has been shown to decrease plasma levels of CETP protein [44] and increase plasma LPL activity, irrespective of changes in weight. We have previously reported that there were no ethnic differences in total physical activity in this SA sample [42,43], however we observed that white women participated in more moderate-to-vigorous physical activity during leisure time, and black women participated in moderate physical activity during travel [42,43]. Future studies are required to consider the impact of dietary intake, as well as other lifestyle factors such as physical activity and fitness, on the associations between these genotypes and serum lipid levels.…”
Section: Discussioncontrasting
confidence: 43%
“…We have previously shown that black women consume more energy, particularly as dietary fat, than white women [26,42,43]. However black women consume less protein and more polyunsaturated fatty acids (PUFA) than white women and hence have higher polyunsaturated fatty acid/saturated fatty acid and omega-6/omega-3 ratios than white women [26,42,43]. The higher dietary fat consumed by black women was shown to modulate the relationship between the pro-inflammatory variant in the tumor necrosis factor-a gene (TNFA, rs361525) and serum lipid concentrations [26].…”
Section: Discussionmentioning
confidence: 99%